Dinâmica da comunidade de algas perifíticas em lago temporário do semiárido. - Fernandes, Ubirajara Lima (2019)
Temporary ponds are the most common ecosystems in the world and have a seasonal dynamic that can be influence the structure of biological communities living in these environments. Although they are common ecosystems in semiarid regions, its functioning and the way it influences the ecology of the species that inhabit these environments are still incipient. Therefore, the successional dynamics of the periphytic microalgae was studied in order to add information about the structure of this community of primary producers in this environment. A 30-day in situ experiment was carried out in a temporary pond located in the rural area of the municipality of Pacatuba (Ceará State, Brazil). Changes in the abundance of periphytic microalgae were observed in a successional period that showed the occurrence of alternative stable states in this community. Changes in ecological attributes (e.g. richness, diversity, equitability and biomass) in the early days of colonization indicate that the successional trajectory was strongly influenced in this period. We can observe three alternative states: (I) corresponding to the largest abundance of Coelastrum proboscideum and related to the development of the other algae that make up the periphytic community; (II) stage represented by the highest abundance of Achnanthidium minutissimum, when the community reached its climax; (III) after the decline in the abundance of this diatom, the green algae resumed its increase in abundance, accompanied by the growth of other periphytic algae, thus evidencing the resilience of this community. We conclude that the community of periphytic algae is sensitive to small disturbances, especially those that may occur during the temporary lake drying period, directing this community to present different configurations during the successional period and reflecting in alternative stable states.